Replication of ONYX-015, a Potential Anticancer Adenovirus, Is Independent of p53 Status in Tumor Cells - Rothmann, Thomas (American Society for Microbiology, 1998)
The 55-kDa E1B protein of adenovirus, which binds to and inactivates the tumor suppressor protein p53, is not expressed in the adenoviral mutant termed ONYX-015 (i.e., dl1520). It was reported that the mutant virus due to a deletion in E1B is able to replicate only in cells deficient for wild-type p53. Accordingly, dl1520 is currently being evaluated as a potential tool in the therapy of p53 deficient cancers. In contrast, we report here that dl1520 replicates independently of the p53 status in various tumor cell lines (U87, RKO, A549, H1299, and U373). In addition, the inhibition of p53-mediated transcriptional activation in wild-type p53 containing U2OS cells, by overexpression of a transdominant negative p53 mutant, did not render the cells permissive for dl1520 replication. Finally, we show that, depending on the multiplicity of infection, the deleted virus is able to replicate in and to kill primary human cells. Thus, the molecular basis for the growth differences of dl1520 within different cell types remains to be determined.